Harold Innis on Peter Pond : biography, cultural memory, and the continental fur trade - Innis, Harold A. (Harold Adams), 1894-1952 (McGill-Queen's University Press, 2019)
"Best known for his writings on economic history and communications, Harold Innis also produced a body of biographical work that paid particular attention to cultural memory and how it is enriched by the study of neglected historical figures. In this compelling volume, William Buxton addresses Innis's engagement with the legacy of the fur trader and adventurer Peter Pond. Harold Innis on Peter Pond comprises eight texts by Innis, including his 1930 biography of Pond as well as his writings on the explorer's myriad activities. The book also features a collection of eight letters exchanged between Innis and Florence Cannon, a descendent of Pond with a strong interest in her ancestor's life and times, and an unpublished 1932 article on Pond's 1773-75 activities as a fur trader on the upper Mississippi, written by Innis's former student R. Harvey Fleming. Situating Innis's writings on Pond in relation to his broader body of biographical work, Buxton interprets what these texts tell us about Innis's intellectual practice, historiography, and the writing of biography. The book explores how Innis's perspectives shifted with changing intellectual and political circumstances and shows that his advocacy of Pond as an unrecognized "father of confederation" challenged conventional views of Canadian nation-building. A critical edition of previously overlooked biographical texts, Harold Innis on Peter Pond traces what these writings disclose about the biographer's character and values even as they discuss their subject."--